Neurodegenerative Disorders A Clinical Guide - Hardiman, Orla; Doherty, Colin P.; Elamin, Marwa; Bede, Peter (Springer International Publishing : Imprint: Springer, 2016)
This new edition provides an accessible guide to the commonest neurodegenerative diseases, outlining the main clinical features, treatment options and outcomes of the conditions most frequently encountered in clinical practice. Beginning with an overview of the general principles that underlie degeneration, and the contribution of established and new diagnostics techniques, the book goes on to describe the most common neurodegenerative conditions and, new for the second edition, also HIV dementia and multiple sclerosis. Final chapters cover important management issues including the use of palliative care strategies, biomarkers and neuropsychology. Written by experts in the field internationally Neurodegenerative Disorders, Second Edition is a practical guide for clinicians that will be indispensable for the management of these conditions.